Preparation method and application of heteroatom-doped anthracite-based carbon spheres

By introducing heteroatoms (nitrogen, oxygen, boron, phosphorus) into anthracite-based carbon and preparing heteroatom-doped anthracite-based carbon spheres, the problems of low conductivity and poor rate performance of anthracite-based carbon electrode materials are solved, and high energy is achieved Water-based symmetric supercapacitor electrode material with density and excellent electrochemical properties.

CN119461325APending Publication Date: 2025-02-18ANHUI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411647758.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing anthracite-based carbon electrode materials have low conductivity and poor rate performance, making it difficult to meet the needs of high energy density water-based symmetric supercapacitors.

Method used

Through organic copolymerization reaction, heteroatoms (nitrogen, oxygen, boron, phosphorus) are introduced into anthracite-based carbon to prepare heteroatom-doped anthracite-based carbon spheres to improve their conductivity and electrochemical properties.

Benefits of technology

The conductivity of heteroatom-doped anthracite-based carbon materials and the ability to surface adsorb electrolyte ions are significantly improved, and the electrochemical performance and energy density of its water-based symmetric supercapacitor electrode material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461325A_ABST
    Figure CN119461325A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of heteroatom-doped anthracite-based carbon spheres, and relates to the technical field of water system symmetric supercapacitor electrode materials. According to the preparation method of the heteroatom (nitrogen, oxygen, boron and phosphorus)-doped anthracite-based carbon sphere and the application of the electrode material in the water system symmetric supercapacitor, the heteroatom (nitrogen, oxygen, boron and phosphorus)-doped anthracite-based carbon sphere is prepared by taking anthracite and an organic polymer containing a heteroatom functional group as carbon sources through an organic copolymerization reaction, so that the heteroatom (nitrogen, oxygen, boron and phosphorus)-doped anthracite-based carbon sphere is obtained. And the obtained polymer is subjected to a one-step high-temperature carbonization-inorganic matter activation pyrolysis process to obtain the water system symmetric supercapacitor carbon-based electrode material. The heteroatom (nitrogen, oxygen, boron and phosphorus) doped anthracite-based carbon sphere prepared by the method has the characteristics of high heteroatom doping amount and simple preparation process, and is suitable for popularization and application in the field of energy storage by simulating and representing the rapid charge / discharge and long-term cycle stability of the water system symmetric supercapacitor electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aqueous symmetrical supercapacitor electrode materials, and in particular to a method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization, and application of heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres prepared by the method in aqueous symmetrical supercapacitor electrodes. Background Art

[0002] With the rapid development of the electric vehicle industry and renewable energy (such as wind energy, solar energy, etc.) around the world, aqueous symmetrical supercapacitors have become one of the most promising future energy storage devices due to their safety, high power density output, fast charge / discharge dynamics and ultra-long cycle life. However, aqueous symmetrical supercapacitors have low energy density and are difficult to meet the needs of actual production and life for high energy density energy storage devices. Therefore, it is particularly important to seek aqueous supercapacitors with high energy density.

[0003] Carbon-based materials have the advantages of abundant reserves, simple preparation, low cost, good conductivity, high cycle stability and good safety. However, the narrow microporous pores in carbon-based electrode materials seriously hinder the diffusion dynamics of electrolyte ions, resulting in low energy density. Therefore, it is of great significance to research and develop low-cost carbon-based materials with high capacity, long life and excellent rate performance as electrode materials for aqueous symmetric supercapacitors.

[0004] As a natural carbon source, coal has abundant reserves, low cost and high carbon content. Anthracite is a type of coal with the highest carbon content (88-98%), the lowest impurity content and low pretreatment difficulty. At the same time, anthracite is composed of large molecular condensed aromatic hydrocarbons with a certain structure formed by various functional groups (such as aliphatic) and ether groups bridging or cross-linking, including graphite-like microcrystals and amorphous regions. Oxygen and nitrogen elements exist in the form of functional groups, which enhance the wettability of electrode materials and electrolytes, reduce ion diffusion resistance, and promote rapid ion transfer. Therefore, anthracite has become an important choice for the development of high-performance, low-cost carbon-based electrode materials. However, pure anthracite has low conductivity, poor rate performance, and its specific capacity is difficult to meet the needs of industrial applications.

[0005] At present, heteroatom doping is mostly used to further improve the electrochemical performance of carbon-based materials. Introducing heteroatoms into carbon-based materials can improve the transfer efficiency of electrons and improve the surface properties of carbon-based materials, which is conducive to the full contact between electrodes and electrolytes. Providing defects on the surface of the carbon structure can enhance the adsorption capacity of carbon-based materials for electrolyte ions, thereby improving their electrochemical performance.

[0006] In summary, how to solve the problem of introducing heteroatoms (nitrogen, oxygen, boron, phosphorus) into anthracite-based carbon to improve the electrochemical properties of carbon-based electrode materials has become a difficult problem. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization reaction, preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization reaction method, and introducing heteroatoms (nitrogen, oxygen, boron, phosphorus) into anthracite-based carbon to improve the electrochemical properties of carbon-based electrode materials, thereby increasing the doping amount and energy density of anthracite-based carbon heteroatoms.

[0008] The present invention is achieved through the following technical solutions:

[0009] The present invention provides a method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon balls by organic copolymerization reaction, S1: grinding, crushing and sieving block anthracite to obtain powdered anthracite. S2: placing the powdered anthracite in a mixed solution of concentrated nitric acid and concentrated sulfuric acid for deashing to obtain deashed anthracite. S3: mixing the deashed anthracite with an organic compound containing heteroatoms (nitrogen, oxygen) at a mass ratio of 1:M and performing an organic polymerization reaction to obtain a coal-based polymer and perform drying. S4: mixing the dried coal-based polymer with an inorganic activator (inorganic substance containing boron and phosphorus) at a mass ratio of 1:N, transferring the mixture to a tubular furnace, performing high-temperature heat treatment under an inert atmosphere, and obtaining heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon balls.

[0010] As a preferred technical solution for material preparation in the present invention: when deashing powdered anthracite, the volume ratio of the mixed solution of concentrated nitric acid and concentrated sulfuric acid is 1:1 to 4:1, standing for 12 hours, washing with deionized water until neutral, collecting the obtained solid and placing it in a 100°C oven for drying to obtain powdered anthracite.

[0011] As a preferred technical solution for material preparation in the present invention: when anthracite and an organic compound containing heteroatoms (nitrogen, oxygen) undergo an organic copolymerization reaction, the deashed anthracite and the organic compound containing heteroatoms (nitrogen, oxygen, boron, phosphorus) are in a mass ratio of 1:M, where M is 0.5 to 4.

[0012] As a preferred technical solution for the preparation of the material in the present invention: the organic compound containing heteroatoms (nitrogen, oxygen) is one component or a mixture of multiple components of 2,6-diaminopyridine, p-phenylenediamine, terephthalaldehyde, biphenylenediamine, and biphenyldicarboxaldehyde, an organic compound containing amino and aldehyde functional groups.

[0013] As a preferred technical solution for the preparation of the material in the present invention: the inorganic activator (inorganic substance containing boron and phosphorus) is one component or a mixture of multiple components of hydroxide (KOH, NaOH, LiOH), boric acid (H3BO3), phosphoric acid (H3PO4), and the mass ratio of the coal-based polymer to the inorganic activator (inorganic substance containing boron and phosphorus) is 1:N, in which N is 0.5 to 3.

[0014] As a preferred technical solution for material preparation in the present invention: high-temperature heat treatment process under inert atmosphere: heat treatment is carried out under nitrogen or argon or other inert atmosphere and at a temperature of 600-800°C, and the high-temperature heat treatment is 1-2h.

[0015] As a preferred technical solution for the material preparation in the present invention: the diameter of the anthracite-based carbon spheres doped with heteroatoms (nitrogen, oxygen, boron, phosphorus) is 400-600 nm, the pore size is 0.5-4 nm, and the total doping content of the heteroatom (nitrogen, oxygen, boron, phosphorus) elements is 13-26 at%.

[0016] As a preferred technical solution for the material preparation of the present invention: when KOH is used as the electrolyte, the first cycle discharge specific capacity is 240 to 320 Fg –1 , energy density is 9~12Whkg –1 .

[0017] As a preferred technical solution for the detection device in the present invention: first, anthracite-based carbon balls doped with heteroatoms (nitrogen, oxygen, boron, phosphorus) are ground; then the active material is mixed evenly with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1, and then a film is formed and dried; finally, a circular electrode sheet with a diameter of 8 to 12 mm is obtained by a puncher, and the circular electrode sheet is adhered to a stainless steel mesh current collector by a roller machine with a pressure of 20 MPa to obtain an electrode material for an aqueous symmetrical supercapacitor.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres prepared by the organic copolymerization method of the present invention effectively improve the conductivity of anthracite and its ability to adsorb electrolyte ions on the surface, thereby improving the electrochemical performance of heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon materials as electrode materials for aqueous symmetric supercapacitors.

[0020] 2. The present invention can effectively increase the amount of heteroatom doping, and the preparation process is simple. The rapid charge / discharge and long-term cycle stability of aqueous symmetrical supercapacitor electrode materials are characterized, and are suitable for promotion and application in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a scanning electron microscope (SEM) comparison of anthracite before and after treatment with a mixed solution of concentrated nitric acid and concentrated sulfuric acid. The test results show that the surface of anthracite is smooth and flat before pretreatment, while the surface is rough and has many cracks after treatment with a mixed solution of concentrated nitric acid and concentrated sulfuric acid.

[0022] Figure 2 This is a SEM comparison of the polymer of anthracite and an organic compound containing heteroatoms (nitrogen, oxygen) before and after one-step high-temperature carbonization / activation. The test results show that after anthracite and an organic polymer containing heteroatoms (nitrogen, oxygen) undergo organic copolymerization, a spherical copolymer with a diameter of less than 500nm is obtained, and the spherical copolymer still retains most of its spherical morphology after one-step high-temperature carbonization / activation, and the diameter of the carbon sphere remains within 500nm.

[0023] Figure 3 This is a comparison of the X-ray electron diffraction (XRD) patterns of untreated anthracite, acidified anthracite, and anthracite-based carbon spheres carbonized at 700°C. Figure 3 It can be seen that there is not much difference in the (002) and (100) diffraction peaks before and after anthracite pretreatment. However, after anthracite undergoes organic copolymerization with organic compounds containing heteroatoms (nitrogen, oxygen, boron, phosphorus) and undergoes a one-step high-temperature carbonization / activation, the (002) and (100) diffraction peaks of anthracite-based carbon spheres are more obvious, indicating that anthracite-based carbon spheres are amorphous carbon structures.

[0024] Figure 4 This is the X-ray photoelectron spectrum (XPS) of anthracite and anthracite-based carbon spheres treated with a mixed solution of concentrated nitric acid and concentrated sulfuric acid. Figure 4 It can be seen that the acid-treated anthracite contains only a small amount of oxygen, while the anthracite-based carbon balls contain not only oxygen but also nitrogen, indicating that the introduction of nitrogen is due to the successful organic copolymerization reaction between organic compounds containing heteroatoms (nitrogen and oxygen) and anthracite.

[0025] Figure 5 The anthracite-based carbon sphere electrode material prepared by anthracite polymer and activator at different activation ratios was tested at a current density of 0.5A. –1 The charge and discharge curves of the anthracite-based carbon ball electrode material can be calculated from the figure to be 197Fg –1 When the activation ratio is 1:1, the prepared anthracite-based carbon ball electrode material has the highest specific capacitance.

[0026] Among them, X1-XRD curve of anthracite-based carbon spheres carbonized at 700℃; X2-XRD curve of carbonized anthracite; X3-XRD curve of untreated anthracite; R1-XPS curve of anthracite-based carbon spheres; R2-XPS curve of untreated anthracite; Y1-XPS curve of anthracite-based carbon spheres at a current density of 0.5A when the activation ratio of anthracite polymer to activator is 1:1 –1 The charge / discharge curve of the anthracite-based carbon sphere material at a current density of 0.5A when the activation ratio of Y2-anthracite polymer to activator is 1:0.5 –1 The charge / discharge curve of the anthracite-based carbon sphere material at a current density of 0.5A when the activation ratio of Y3-anthracite polymer to activator is 1:2 –1 The charge / discharge curve of Y4-anthracite-based carbon ball material at a current density of 0.5Ag -1 The charge / discharge curves. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0028] Embodiment 1

[0029] 1 g of anthracite is ground and sieved to obtain powdered anthracite; the powdered anthracite is dispersed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:1 for deashing, allowed to stand for 12 hours, washed with a large amount of deionized water until neutral, the obtained solid is collected and placed in an oven at 100°C for drying to obtain deashed anthracite.

[0030] The deashed anthracite, 2,6-diaminopyridine and terephthalaldehyde are mixed in a mass ratio of 1:1:1 and subjected to an organic polymerization reaction. The reaction product is collected and dried. The dried coal-based polymer is mixed with potassium hydroxide (KOH) in a mass ratio of 1:0.5 and dried in an oven at 100°C. After drying, it is transferred to a tubular furnace and heat treated at 600°C for 2h under an inert atmosphere to obtain nitrogen and oxygen co-doped anthracite-based carbon balls.

[0031] The anthracite-based carbon balls co-doped with nitrogen and oxygen are ground, and then the active material is evenly mixed with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1 to form a film and dry it. A circular electrode sheet with a diameter of 18 to 12 mm is obtained by a puncher, and the circular electrode sheet is adhered to a stainless steel mesh current collector on a double-roll machine with a pressure of 20 MPa, thereby preparing a water-based symmetrical supercapacitor electrode material.

[0032] Embodiment 2

[0033] 1 g of anthracite is ground and sieved to obtain powdered anthracite; the powdered anthracite is dispersed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2 for deashing, allowed to stand for 12 hours, washed with a large amount of deionized water until neutral, the obtained solid is collected and placed in an oven at 100°C for drying to obtain deashed anthracite.

[0034] The deashed anthracite, p-phenylenediamine and terephthalaldehyde are mixed in a mass ratio of 1:1:1 and subjected to an organic polymerization reaction. The reaction product is collected and dried. The dried coal-based polymer is mixed with sodium hydroxide (NaOH) in a mass ratio of 1:1 and dried in an oven at 100°C. After drying, the mixture is transferred to a tubular furnace and heat treated at 700°C for 2h under an inert atmosphere to obtain nitrogen and oxygen co-doped anthracite-based carbon balls.

[0035] The anthracite-based carbon balls co-doped with nitrogen and oxygen are ground, and then the active material is evenly mixed with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1 to form a film and dry it. A circular electrode sheet with a diameter of 8 to 12 mm is obtained by a puncher, and the circular electrode sheet is adhered to a stainless steel mesh current collector on a double-roll machine with a pressure of 20 MPa, thereby preparing a water-based symmetrical supercapacitor electrode material.

[0036] Embodiment 3

[0037] 2 g of anthracite was ground and sieved to obtain powdered anthracite; the powdered anthracite was dispersed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:1 for deashing, allowed to stand for 12 hours, washed with a large amount of deionized water until neutral, the obtained solid was collected and placed in an oven at 100°C for drying to obtain deashed anthracite.

[0038] The deashed anthracite, p-phenylenediamine and p-terephthalaldehyde are mixed uniformly in a mass ratio of 1:3:1 and subjected to an organic polymerization reaction. The reaction product is collected and dried. The dried coal-based polymer is mixed with boric acid (H3BO3) in a mass ratio of 1:1 and dried in an oven at 100°C. After drying, the mixture is transferred to a tubular furnace and heat treated at 600°C for 2h under an inert atmosphere to obtain nitrogen, oxygen and boron co-doped anthracite-based carbon balls.

[0039] Anthracite-based carbon balls co-doped with nitrogen, oxygen and boron are ground, and then the active material is evenly mixed with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1 to form a film and dry it. A circular electrode sheet with a diameter of 8 to 12 mm is obtained by a puncher, and the circular electrode sheet is adhered to a stainless steel mesh current collector on a double-roll machine with a pressure of 20 MPa, thereby preparing a water-based symmetrical supercapacitor electrode material.

[0040] Embodiment 4

[0041] 2 g of anthracite was ground and sieved to obtain powdered anthracite; the powdered anthracite was placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:2 for deashing, allowed to stand for 12 hours, washed with a large amount of deionized water until neutral, the obtained solid was collected and placed in an oven at 100°C for drying to obtain deashed anthracite.

[0042] The deashed anthracite, diphenylene glycol and terephthalaldehyde are mixed in a mass ratio of 1:1:3 and subjected to an organic polymerization reaction. The reaction products are collected and dried. The dried coal-based polymer is mixed with phosphoric acid (H3PO4) in a mass ratio of 1:2 and dried in an oven at 100°C. After drying, the mixture is transferred to a tubular furnace and heat treated at 600°C for 2 hours under an inert atmosphere to obtain nitrogen, oxygen and phosphorus co-doped anthracite-based carbon balls.

[0043] Anthracite-based carbon balls co-doped with nitrogen, oxygen and phosphorus are ground, and then the active material is evenly mixed with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1 to form a film and dry it. A circular electrode sheet with a diameter of 8 to 12 mm is obtained by a puncher, and the circular electrode sheet is adhered to a stainless steel mesh current collector on a double-roll machine with a pressure of 20 MPa, thereby preparing a water-based symmetrical supercapacitor electrode material.

[0044] Embodiment 5

[0045] 1.5 g of anthracite was ground and sieved to obtain powdered anthracite; the powdered anthracite was placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:1.5 for deashing, allowed to stand for 12 hours, washed with a large amount of deionized water until neutral, the obtained solid was collected and placed in an oven at 100°C for drying to obtain deashed anthracite.

[0046] The deashed anthracite, diphenylene glycol, biphenyl formaldehyde are mixed evenly in a mass ratio of 1:2:1 and subjected to an organic polymerization reaction. The reaction products are collected and dried. The dried coal-based polymer is mixed with phosphoric acid (H3PO4) in a mass ratio of 1:1 and dried in an oven at 100°C. After drying, the mixture is transferred to a tubular furnace and heat treated at 700°C for 2 hours under an inert atmosphere to obtain nitrogen, oxygen, and phosphorus co-doped anthracite-based carbon balls.

[0047] Anthracite-based carbon balls co-doped with nitrogen, oxygen and phosphorus are ground, and then the active material is evenly mixed with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1 to form a film and dry it. A circular electrode sheet with a diameter of 8 to 12 mm is obtained by a puncher, and the circular electrode sheet is adhered to a stainless steel mesh current collector on a double-roll machine with a pressure of 20 MPa, thereby preparing a water-based symmetrical supercapacitor electrode material.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization, characterized in that: S1: Grinding, crushing and sieving lump anthracite to obtain powdered anthracite; S2: dispersing powdered anthracite in a mixed solution of concentrated nitric acid and concentrated sulfuric acid for deashing to obtain deashed anthracite; S3: mixing the deashed anthracite and an organic compound containing heteroatoms (nitrogen, oxygen) in a mass ratio of 1:M and performing an organic polymerization reaction to obtain a coal-based polymer and drying the mixture; S4: The dried coal-based polymer is mixed with an inorganic activator (inorganic substances containing boron and phosphorus) in a mass ratio of 1:N, and transferred to a tubular furnace for high-temperature heat treatment under an inert atmosphere to obtain heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon balls.

2. The method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization according to claim 1, characterized in that: During the deashing treatment of powdered anthracite, the volume ratio of the mixed solution of concentrated nitric acid and concentrated sulfuric acid is 1:1 to 4:1, and the mixture is allowed to stand for 12 hours, washed with deionized water until neutral, and the obtained solid is collected and placed in an oven at 100°C for drying to obtain powdered anthracite.

3. The method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization according to claim 1, characterized in that: When anthracite and an organic compound containing heteroatoms (nitrogen, oxygen) undergo an organic copolymerization reaction, the deashed anthracite and the organic compound containing heteroatoms (nitrogen, oxygen, boron, phosphorus) are in a mass ratio of 1:M, where M is 0.5 to 4.

4. The method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization according to claim 1 or 3, characterized in that: The organic compound containing heteroatoms (nitrogen, oxygen) is one component or a mixture of multiple components of 2,6-diaminopyridine, p-phenylenediamine, terephthalaldehyde, biphenylenediamine, and biphenyldicarboxaldehyde, an organic compound containing amino and aldehyde functional groups.

5. The method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization according to claim 1, characterized in that: The inorganic activator (inorganic substance containing boron and phosphorus) is one component or a mixture of multiple components of hydroxide (KOH, NaOH, LiOH), boric acid (H3BO3, NaBH4), phosphoric acid (H3PO4, NaH2PO4), and the mass ratio of the coal-based polymer to the inorganic activator (hydroxide, inorganic substance containing boron and phosphorus) is 1:N, in which N is 0.5 to 3.

6. The method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization according to claim 1, characterized in that: The high-temperature heat treatment process under the inert atmosphere is as follows: heat treatment is performed under nitrogen or argon or other inert atmospheres at a temperature of 600 to 800° C., and the high-temperature heat treatment time is 1 to 2 hours.

7. The method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon spheres by organic copolymerization according to claim 1, characterized in that: The diameter of the heteroatom (nitrogen, oxygen, boron, phosphorus) doped anthracite-based carbon sphere is 400-600 nm, the pore size is 0.5-4 nm, and the total doping content of the heteroatom (nitrogen, oxygen, boron, phosphorus) elements is 13-26 at%.

8. A water-based symmetric supercapacitor assembled with heteroatom (nitrogen, oxygen, boron, phosphorus)-doped anthracite-based carbon spheres as electrode materials prepared by the method for preparing heteroatom (nitrogen, oxygen, boron, phosphorus)-doped anthracite-based carbon spheres by an organic copolymerization reaction according to any one of claims 1 to 7, characterized in that: When KOH is used as the electrolyte, the first cycle discharge capacity is 240~320Fg –1 , energy density is 9~12Whkg –1 .

9. A process for preparing anthracite-based carbon spheres doped with heteroatoms (nitrogen, oxygen, boron, phosphorus) by an organic copolymerization reaction according to any one of claims 1 to 7, using heteroatoms (nitrogen, oxygen, boron, phosphorus) doped with anthracite-based carbon spheres as electrode materials for aqueous symmetric supercapacitors, characterized in that: Firstly, the anthracite-based carbon spheres doped with heteroatoms (nitrogen, oxygen, boron, phosphorus) were ground; Then the active material is mixed with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1, and then film-formed and dried; Finally, a circular electrode sheet with a diameter of 8 to 12 mm is obtained by using a puncher, and the circular electrode sheet is adhered to a stainless steel mesh current collector on a roller machine with a pressure of 20 MPa, thereby obtaining an aqueous symmetrical supercapacitor electrode material.